2002
DOI: 10.1128/aem.68.2.642-649.2002
|View full text |Cite
|
Sign up to set email alerts
|

Tetrachloroethene Dehalorespiration and Growth of Desulfitobacterium frappieri TCE1 in Strict Dependence on the Activity of Desulfovibrio fructosivorans

Abstract: Tetrachloroethene (PCE) dehalorespiration was investigated in a continuous coculture of the sulfatereducing bacterium Desulfovibrio fructosivorans and the dehalorespiring Desulfitobacterium frappieri TCE1 at different sulfate concentrations and in the absence of sulfate. Fructose (2.5 mM) was the single electron donor, which could be used only by the sulfate reducer. With 2.5 mM sulfate, the dehalogenating strain was outnumbered by the sulfate-reducing bacterium, sulfate reduction was the dominating process, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 41 publications
(34 reference statements)
0
30
0
Order By: Relevance
“…This approach of defined syntrophic growth enabled direct experimental measurement of the specific effects of associated bacteria on the growth, activity and gene expression of Dehalococcoides, similar to the approach taken for the study of Syntrophomonas wolfei with Methanospirillum hungatei (Beaty and McInerney, 1989), for the study of D. vulgaris with methanogens (Bryant et al, 1977;Scholten et al, 2007;Stolyar et al, 2007;Walker et al, 2009) and for the study of Desulfovibrio sp. strain SULF1 and Desulfovibrio fructosivorans with a dehalorespiring bacterium Desulfitobacterium frappieri TCE1 (Drzyzga et al, 2001;Drzyzga and Gottschal, 2002). In DE195/DVH and DE195/DVH/MC, the dechlorination rates of DE195 were enhanced 2-to 3-fold over the isolate and cell yields were enhanced in the co-culture by B1.5 times.…”
Section: Discussionmentioning
confidence: 81%
“…This approach of defined syntrophic growth enabled direct experimental measurement of the specific effects of associated bacteria on the growth, activity and gene expression of Dehalococcoides, similar to the approach taken for the study of Syntrophomonas wolfei with Methanospirillum hungatei (Beaty and McInerney, 1989), for the study of D. vulgaris with methanogens (Bryant et al, 1977;Scholten et al, 2007;Stolyar et al, 2007;Walker et al, 2009) and for the study of Desulfovibrio sp. strain SULF1 and Desulfovibrio fructosivorans with a dehalorespiring bacterium Desulfitobacterium frappieri TCE1 (Drzyzga et al, 2001;Drzyzga and Gottschal, 2002). In DE195/DVH and DE195/DVH/MC, the dechlorination rates of DE195 were enhanced 2-to 3-fold over the isolate and cell yields were enhanced in the co-culture by B1.5 times.…”
Section: Discussionmentioning
confidence: 81%
“…For our experimental system, segregating metabolic processes eliminates inter-enzyme competition and consequently reduces the accumulation of intermediates, thus accelerating the consumption of substrates that produce growth-inhibiting intermediates. This principle has previously only been supported by anecdotal evidence (de Souza et al, 1998;Møller et al, 1998;Pelz et al, 1999;Drzyzga and Gottschal 2002;Holmes et al, 2006) while direct experimental evidence has so far been lacking, thus reflecting an important gap in our knowledge about the consequences of metabolic specialization on microbial processes.…”
Section: Discussionmentioning
confidence: 91%
“…Empirical evidence to support this prediction, however, remains anecdotal. For example, while substrate cross-feeding is often observed for the consumption of environmental pollutants that produce toxic and growth-inhibiting intermediates (de Souza et al, 1998;Møller et al, 1998;Pelz et al, 1999;Drzyzga and Gottschal 2002;Holmes et al, 2006), there is no empirical evidence that substrate cross-feeding itself accelerates the consumption of those pollutants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in mixed cultures that can fully degrade PCE to ethene, two or more organisms are likely involved. Isolates of the genera Dehalobacter (29,56), Desulfitobacterium (13,21,40,51), Desulfuromonas (50), and Sulfospirillum (37) can grow through the dechlorination of PCE or TCE to cDCE, but dechlorination does not proceed further. Here it has been found that in the WL cultures dechlorination of 1,1,2-TCA proceeds through an analogous situation: 1,1,2-TCA was initially transformed to VC by a Dehalobacter sp., but VC was only degraded by the Dehalococcoides sp., as each organism only grew significantly during the respective dechlorination steps.…”
Section: Discussionmentioning
confidence: 99%